Comparable reductions in hyperpnoea-induced bronchoconstriction and markers of airway inflammation after supplementation with 6·2 and 3·1 g/d of long-chain n-3 PUFA in adults with asthma - Williams, Neil C.; Hunter, Kirsty A.; Shaw, Dominick E.; Jackson, Kim G.; Sharpe, Graham R.; Johnson, Michael A. (Cambridge University Press, 2017)
Although high dose n-3 PUFA supplementation reduces exercise- and hyperpnoea-induced bronchoconstriction (EIB/HIB), there are concurrent issues with cost, compliance and gastrointestinal discomfort. It is thus pertinent to establish the efficacy of lower n-3 PUFA doses. Eight male adults with asthma and HIB and eight controls without asthma were randomly supplemented with two n-3 PUFA doses (6·2 g/d (3·7 g EPA and 2·5 g DHA) and 3·1 g/d (1·8 g EPA and 1·3 g DHA)) and a placebo, each for 21 d followed by 14 d washout. A eucapnic voluntary hyperpnoea (EVH) challenge was performed before and after treatments. Outcome measures remained unchanged in the control group. In the HIB group, the peak fall in forced expiratory volume in 1 s (FEV1) after EVH at day 0 (−1005 (sd 520) ml, −30 (sd 18) %) was unchanged after placebo. The peak fall in FEV1 was similarly reduced from day 0 to day 21 of 6·2 g/d n-3 PUFA (−1000 (sd 460) ml, −29 (sd 17) % v. −690 (sd 460) ml, −20 (sd 15) %) and 3·1 g/d n-3 PUFA (−970 (sd 480) ml, −28 (sd 18) % v. −700 (sd 420) ml, −21 (sd 15) %) (P<0·001). Baseline fraction of exhaled nitric oxide was reduced by 24 % (P=0·020) and 31 % (P=0·018) after 6·2 and 3·1 g/d n-3 PUFA, respectively. Peak increases in 9α, 11β PGF2 after EVH were reduced by 65 % (P=0·009) and 56 % (P=0·041) after 6·2 and 3·1 g/d n-3 PUFA, respectively. In conclusion, 3·1 g/d n-3 PUFA supplementation attenuated HIB and markers of airway inflammation to a similar extent as a higher dose. Lower doses of n-3 PUFA thus represent a potentially beneficial adjunct treatment for adults with asthma and EIB.